Personalities of domestic aircraft construction: Gindin Gilil Peisakhovich - Kryvokon, O. H. (History of science and technology, 2018)
The publication is devoted to the analysis of the biography and creativity of Gilil Pesakhovich Gindin (1923 – 1998), the designer in the field of domestic aircraft engineering, a specialist in the development of the aircraft wing. In the national history of science and technology, in particular in the aircraft engineering industry, there is almost no information about the biographies, design, technical, engineering or other achievements of those people who under the guidance of O.K. Antonov, created the world-famous domestic transport aircraft. For various reasons, the vast majority of those who directly develop and create airplanes remain in the shadow of the names of general designers - top managers. Therefore, we decided to devote a number of publications to research and description of the domestic aircraft industry personalities. On the basis of personal documents, interview materials of colleagues, contemporaries and information kindly provided by Gilil Peisakhovich’s son, the life path and facts characterizing Gindin G.P. professional achievements during his work at the enterprise, both under the guidance of O.K. Antonov, and afterwards are reproduced. Namely, data on the exploits of G. P. Gindin during the Great Patriotic War are presented, and a list of his military awards is given. Gilil Peisakhovich’s career path is described from a rank-and-file worker, a designer in the wing department to the brigade chief and the head of the KV-22 department. The main design achievements and innovative developments of Gindin G.P. are briefly described. In particular, the fact that with his direct participation the pressed panels of the wing with a length of 28 meters with one ending for the AN-124 "Ruslan" were developed, designed and worked out in production, which is listed in the Guinness Book of Records as a wing, which passed the entire stage of life tests without a single remark and breakdown. For the first time, some little-known data on the activities of the wing department and other features of the creation of the world-famous AN-124 "Ruslan" aircraft are published. In addition, the memoirs of contemporaries about personal, organizational, managerial and business qualities of a famous aircraft manufacturer are given. The publication concluded that Gilil Peisakhovich Gindin undoubtedly made a significant contribution to the development of the domestic aircraft industry, in particular in the field of designing, developing and improving the wing and its mechanization.